Perilaku Pembelian Konsumen Sepeda Motor Honda di Manado - Grace Sumakul (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
After covid-19 hit the world, the economy and consumer behavior changed utterly. This research examines consumer purchasing behavior towards Honda Matic motorcycles in Manado City based on demographic, psychological, information sources, and consumer expectation. The study found that men who were less than 34 years old and came from the middle class were most motorcycle buyers. Buyers themselves decide to buy a motorcycle because it is more economical and comfortable to use by themselves in supporting work activities because motorcycles are faster than other vehicles. The source of consumer information about motorcycles comes from friends and family, consumers will conduct searches on the internet. Consumers expect a comfortable waiting room with guaranteed service as well as discounts and better designs in the future. Social media is expected to be a source of information on motorcycles and dealers will remain the location for purchasing motorcycles later. Companies can create marketing strategies to attract different consumers while retaining existing consumers. Companies can make aggressive promos on the internet such as guaranteed service discounts and attractive image designs. The role of the dealer and the influence of word of mouth of friends and family needs to be maintained so dealer satisfaction can increase.